Phraseological and Lexical Control of Time Units in English and Uzbek (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The theory of phraseological units in world linguistics, the formation of phraseological units in the language in modern linguistics, the cultural aspect of the relationship between language and culture, a rich vocabulary and phraseological units related to time measurement in English and Uzbek, time measurement in English a number of phraseological units related to, a number of phraseological units related to time measurement in the Uzbek language.